Identification of tyrosinase inhibitors from Glycyrrhiza uralensis - Kim, HJ; Seo, SH; Lee, BG; Lee, YS (GEORG THIEME VERLAG KG, 2005)
Tyrosinase is a key enzyme in the production of melanins. Phytochemical studies of a Glycyrrhiza uralensis extract were performed by measuring the tyrosinase and melanin synthesis inhibitory activity. Glycyrrhisoflavone and glyasperin C were identified as tyrosinase inhibitors for the first time. Glyasperin C showed a stronger tyrosinase inhibitory activity (IC50 = 0.13 0.01 mu g/mL) than glabridin (IC50 = 0.25 +/- 0.01 mu g/mL) and a moderate inhibition of melanin production (17.65 +/- 8.8 % at 5 mu g/mL). Glycyrrhisoflavone showed a strong melanin synthesis inhibitory activity (63.73 +/- 6.8 % inhibition at 5 mu g/mL). These results suggest that glyasperin C and glycyrrhisoflavone could be promising candidates in the design of skin-whitening agents.
Keywords: FLAVONOIDS; PIGMENTATION; CONSTITUENTS; ACID